POLITIK PENDIDIKAN MADRASAH DI INDONESIA PASCA KEMERDEKAAN: 1945 – 2003 - Ismail Sukardi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2010)
The research aims to comprehend the phenomenon of educational politics of madrasah in Indonesia since the begining of independence till 2003, when new National Education Bill released. The research finds as follow: in the Old Order government period, the educational politics of madrasah begin from the effort of relegious department to integrate madrasah as one of national education system. In the New Order government period one of madrasah’s policies is uniformity of curriculum between madrasah and general school. Every single of educational policy toward madrasah result the implications in every part or dimensions of madrasah. The policies have many consequences in management, curriculum, financial and facilties of madrasah.